THE CULTURAL VALUES OF THE BULANGAN LONDONG SEMBANGAN SUKE BARATA RITUAL OF THE INDIGENOUS PEOPLE OF TORAJA - Markus Deli Girik Allo; Nilma Taula’bi; Elim Trika Sudarsih; Eka Prabawati Rum (Balai Pelestarian Nilai Budaya Jawa Barat, 2021)
The purpose of this study was to investigate the cultural values in the ritual of Bulangan Londong Sembangan Suke Barata as part of the Toraja indigenous people life. The research method used in this study is a qualitative method. Meanwhile, the respondents involved in this study include culturist, linguists, and the Toraja community. The research instruments used in this study were document files, interviews with the subjects, and observations using a video recorder that recorded the ritual process of Bulangan Londong Sembangan Suke Barata. The data analysis technique in this study includes three main steps, namely data reduction, data presentation, and drawing conclusions. The results showed that the cultural values contained in the rituals of the Bulang Londong Sembangan Suke Barata were 'Manuk' which symbolized the value of the work ethic, 'Ussembang Suke Barata' which represented the religious value of bamboo slashed by 'Mina', and 'Kayunan Londong' which personifies the leader's patriotic value.Tujuan dari penelitian ini adalah untuk menyelidiki nilai-nilai budaya dari ritual bulangan londong sembangan suke barata dari masyarakat adat Toraja. Penelitian ini menggunakan metode kualitatif. Responden penelitian ini adalah budayawan, ahli bahasa, dan komunitas Toraja. Instrumen penelitian yang digunakan adalah file dokumen, wawancara dengan subjek, dan pengamatan dengan menggunakan perekam video pada ritual bulangan londong sembangan suke barata. Teknik analisis data mencakup tiga langkah utama, pengurangan data, presentasi data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa nilai-nilai budaya yang terkandung dalam ritual bulangan londong sembangan suke barata adalah manuk yang melambangkan nilai etos kerja, ussembang suke barata yang mewakili nilai religius bambu yang ditebas oleh mina, dan kayunan londong sebagai personifikasi nilai patriotik pemimpin.